Evolution and development of forest harvesting in Peninsular Malaysia - Kamarudin, Norizah; Ismail, Mohd Hasmadi; Jusoff, Kamaruzaman; Mohd Sood, Alias (Forestry Department Peninsular Malaysia, 2011)
Since its inception in 1978, Malaysian forest is now managed under sustainable forest management by adopting Selective Management System practices which consider reduced impact logging and Malaysian Criteria and Indicator to meet international requirements and forest certification. With regards to sustainable forest management, evolution can be seen in forest operation activities, where the high impact of conventional logging especially to the forest ecosystem has been transformed into reduced impact logging practices and the geoinformatics technology application. This paper attempts to review and discuss the evolution and development phases in forest harvesting, and how they will shape the future forest operation in Peninsular Malaysia. All forest engineering activities such as forest resource surveying and harvest planning, forest road planning and construction should synchronise with the environmental protection as practised by the Forestry Department Peninsular Malaysia towards sustainable forest management. Thus, the environmentally sound, low cost and high efficient techniques of forest engineering and operation will be the key points of research in the future.